Handbook of biofuels production : processes and technologies - Luque, Rafael; Lin, Carol Sze Ki (Chemist); Wilson, Karen (Professor); Du, Chenyu (Woodhead Publishing, 2023)
Handbook of Biofuels Production: Processes and Technologies, Third Edition provides a comprehensive and systematic reference on a range of biomass conversion processes and technologies. In response to the global increase in the use of biofuels as substitute transportation fuels, advanced chemical, biochemical and thermochemical biofuels production routes are quickly being developed. Substantial additions for this new edition include increased coverage of emerging feedstocks, including microalgae, more emphasis on by-product valorization for biofuels' production, additional chapters on emerging biofuel production methods, and co-production of biofuels and bioproducts. The book's editorial team is strengthened by the addition of an extra member, and a number of new contributors have been invited to work with authors from the first and second edition to revise existing chapters, with each offering fresh perspectives. This book is an essential reference for professional engineers in the biofuel industry as well as researchers in academia, from post-graduate level and up.
Keywords: Biomass energy.; elektronické knihy; electronic books